Teachers’ Improvisation of Instructional Materials and Mathematics Learning Gains among Students in Kwara State: Counselling Implications - Olanrewaju, Muraina Kamilu; Ibrahim, Umar Talatu; Verma, Kirti (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
The purpose of this study was to investigate the assessment of teachers’ improvisation and utilisation of instructional materials as determinants of mathematics learning gains among secondary school students in Kwara State: Counselling Implications. Descriptive research design of ex-post-facto type was used in the study. Three hundred and seventy two respondents were selected randomly from 10 Local Government Area in Kwara State, Nigeria. The respondents were measured with validated scale and the data obtained was analyzed using the Pearson Product Moment Correlation (PPMC) and Multiple regression statistical analysis. Three research questions were raised and answered in the study. The result showed that mathematics learning gains among secondary school students is significantly correlated with teachers’ improvisation of instructional materials (r = .863; p<.05) and teachers’ utilisation of instructional materials (r= .783; p<.05), the independent variables when pulled together have significant effect on mathematics learning gains (R (adjusted) =.837 & R2 (adjusted) =.745) with 74.5% variance accounted for mathematics learning gains and each of the independent variables made a significant contribution to the prediction of mathematics learning gains. In view of these findings, the study recommended that relevant professional bodies like mathematics Association of Nigeria (MAN) and Counselling Association of Nigeria (CASSON) should organize seminar or workshops during annual conferences to train teachers about the techniques that will be used to bring a total change in teaching mathematics contents.